"I Have Actually not Lost any Adolescent Since I Started Engaging Them one on one:" Training Satisfaction and Subsequent Practice among Health Providers Participating in a Standardized Patient Actor Training to Improve Adolescent Engagement in HIV Care. (January 2022) - Okinyi, Hellen M.; Wachira, Cyrus M.; Wilson, Kate S.; Nduati, Margaret N.; Onyango, Alvin D.; Mburu, Caren W.; Inwani, Irene W.; Owens, Tamara L.; Bukusi, David E.; John-. Stewart, Grace C.; Wamalwa, Dalton C.; Kohler, Pamela K.
Background: Poor health care worker (HCW) interactions with adolescents negatively influence engagement in HIV care. We assessed the impact of standardized patient actor training on HCW competence in providing adolescent HIV care in Kenya. Methods: We conducted pre-post cross-sectional surveys and qualitative exit interviews during a stepped wedge randomized trial. Cross-sectional surveys assessed self-rated competence in providing adolescent services before and after the intervention, and training satisfaction. In-depth interviews with a subset of HCW participants one year after training. Results: Over 90% of HCWs reported satisfaction with the training and there was significant improvement in self-rated competence scores (mean = 4.63 [highest possible score of 5] post-training vs 3.86 pre-training, p < 0.001). One-year following training, HCWs reported using skills in patient-centered communication and structuring an adolescent clinical encounter. Conclusions: This SP training intervention improved self-rated competence and showed sustained perceived impact on HCW skills in adolescent HIV service provision one year later.